Influência do tratamento térmico assistido por pressão nas propriedades óptica e elétrica do trióxido de tungstênio - Pimenta, Juliana de Oliveira [UNESP] (2015)
The aim of this work is to study the influence of a pressure-assisted heat treatment on the electrical and optical properties of nanoparticulate tungsten trioxide (WO3) obtained by microwave assisted hydrothermal method. The behavior of WO3 as gas sensor and its pholominescence emission were used to evaluate the electrical and optical properties, respectively. Samples were heat-treated under an air pressure of 2 MPa at 180ºC for 32 h. The oxides obtained were previously characterized by X-ray diffraction (XRD), nitrogen adsorption volumetric (BET), X-ray Photoelectron Spectroscopy (XPS), and field emission scanning electron microscopy (FEG-SEM) and micro Raman Spectroscopy. Using combined techniques, the structure, morphology, size and chemical composition of the synthetized materials were characterized in details. A comparison between samples that underwent the pressure-assisted heat treatment and samples that underwent a conventional heat treatment was established. The originality of the work is to understand how the pressure-assisted heat treatment chames the tungsten trioxide behavior without the addition of dopants. The photoluminescence emission intensity increased after the pressure treatment, and the maximum emission changed from 460 nm (blue) to 549 nm (green). The spectrum exhibited a red shift at higher wavelengths. This displacement and change in intensity can be correlated to a decrease in oxygen vacancies after the pressure-assisted heat treatment. In addition, the electrical properties were investigated as a n-type gas sensor for NO2 and H2 that are reducing and oxidizing gases, respectively. Samples became more resistive to electric current impeding the investigation of the sensing properties of the oxide under study.